On complex Langevin dynamics and zeroes of the measure II: Fermionic determinant - Gert Aarts (Proceedings of Science (Lattice 2016), 2016)
Lattice QCD at non-vanishing chemical potential is studied using the complex Langevin equation (CLE). One of the conditions for the correctness of the results of the CLE is that the zeroes of the measure coming from the fermionic determinant are outside of the distribution of the configurations, or at least in a region where support for the distribution is very much suppressed. We investigate this issue for Heavy Dense QCD (HDQCD) and full QCD at high temperatures. In HDQCD it is found that the configurations move closest to the zeroes of the measure around the critical chemical potential of the onset transition, where the sign problem is diminished, but results remain largely unaffected. In full QCD at high temperatures the investigation of the spectrum of the Dirac operator yields a similar observation: the results are unaffected by the issue of the poles.